2006
DOI: 10.1111/j.1538-7836.2006.02175.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine differentially interacts with tumor necrosis factor‐α and thrombin in endothelial tissue factor induction: the role of c‐Jun NH2‐terminal kinase

Abstract: Summary.  Background: Histamine plays an important role in vascular disease. Tissue factor (TF) expression is induced in vascular inflammation and acute coronary syndromes. Objectives: This study examined the effect of histamine on tumor necrosis factor‐α‐ (TNF‐α‐) vs. thrombin‐induced endothelial TF expression. Methods and results: Histamine (10−8–10−5 mol L−1), TNF‐α (5 ng mL−1), and thrombin (1 U mL−1) induced TF expression in human endothelial cells. Although TF expression by TNF‐α and thrombin was identic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
0
11
1
Order By: Relevance
“…Previous reports have shown that TNF-a enhances induction of TF by histamine and thrombin in a concentration-dependent manner, and was amplified by paclitaxel. 22 Other reports also showed that expression of TNF-a receptor-1 in arterial walls accelerate atherosclerotic lesions. 8 The coagulation cascade results in the deposition of fibrin, which is cleared by tissue plasminogen activator released from endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have shown that TNF-a enhances induction of TF by histamine and thrombin in a concentration-dependent manner, and was amplified by paclitaxel. 22 Other reports also showed that expression of TNF-a receptor-1 in arterial walls accelerate atherosclerotic lesions. 8 The coagulation cascade results in the deposition of fibrin, which is cleared by tissue plasminogen activator released from endothelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…Histamine-induced vascular contractions, 11,17 as well as expression of tissue factor 12,13 , a key trigger of the coagulation cascade, are mediated via this receptor. In line with these findings, the present data indicate that activation of the H1 receptor, but not the H2 receptor, promotes the formation of atherosclerotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine has been shown to induce the expression of TF in vascular cells activating the H1, but not the H2, receptor (59, 60), revealing the potential effect of histamine on the extrinsic coagulation pathway. Some newly generated cytokines from mast cells, such as IL-6, also affect the coagulation system.…”
Section: The Coagulation System In Anaphylaxismentioning
confidence: 99%